PRODUKSI IKAN BANDENG TANPA DURI (Chanos chanos) BAGI MASYARAKAT DESA TAMANGAPA KABUPATEN PANGKEP PROPINSI SULAWESI SELATAN - Muhammad Ikhsan Wamnebo; Kasmawati Kasmawati (Politeknik Kelautan dan Perikanan Sorong, 2021)
The problem experienced by the milkfish (Chanos chanos) farming community in Tamangapa Village, Pangkep Regency is the low selling price of milkfish which is cheap. This is because milkfish has so many spines that people don't like it, even though milkfish has good nutritional value, especially omega-3 unsaturated fatty acids (ω3) reaching 14.2% and protein content of 20%. This activity aims to increase the selling value of milkfish through training activities to remove milkfish spines. The method used is training and assistance in removing the thorns of milkfish, which is attended by PKK women, village office employees, and local people who have the desire to become entrepreneurs. The result is that thornless milkfish can be sold to consumers or processed into products such as nuggets, meatballs, and crispy milkfish. The conclusion is milkfish without spines has a profitable business opportunity with an increase in selling prices, so that it can increase the income of fish farmers in Tamangapa Village, Pangkep Regency.